Racial and Ethnic Disparities in Treatment Initiation Among Patients with Newly Diagnosed Psoriatic Arthritis: A Retrospective Medicaid Claims Database Study - Aarti A. Patel; Shannon Allen Ferrante; Iris Lin; Alex Z. Fu; Alicia K. Campbell; Arlene Tieng (Rheumatology and Therapy, 2023)
Abstract Introduction In patients with psoriatic arthritis (PsA), potential differences in care by race/ethnicity have not been well studied. Methods This retrospective, observational cohort analysis utilized the IBM MarketScan® Multi-State Medicaid database. Patients aged ≥ 18 years with two or more PsA-related claims between January 1, 2010 and December 31, 2019, and ≥ 12 months of continuous enrollment before the first diagnosis of PsA (index date) were included. Outcomes evaluated were the use of disease-modifying antirheumatic drugs (DMARDs) overall and by type (conventional synthetic, biologic, targeted synthetic) within 12 months following initial PsA diagnosis, as well as the time to DMARD initiation after initial PsA diagnosis, stratified by race/ethnicity. Multivariate Cox proportional hazards models were used to assess potential associations between patient baseline characteristics and time to DMARD initiation. Results Among patients with newly diagnosed PsA (N = 3432), the mean age was 44.4 years, 69.9% were female, 77.4% were White, and 10.1% were Black. Of the 2993 patients with at least 12 months of follow-up, fewer Black patients received any DMARD therapy compared with White patients (68.4 vs. 76.4%, respectively, p = 0.002), and, specifically, a lower percentage of Black patients received biologic DMARDs compared with White patients (33.6 vs. 42.6%, respectively, p = 0.003). After adjusting for baseline characteristics, Black patients had significantly longer time to initiation of any DMARD (HR [95% CI] 0.82 [0.71–0.94]) and biologic DMARD (0.84 [0.71–0.99]) compared with White patients. Other baseline variables such as older age, anxiety, and hepatitis C were also significantly associated with longer time to any DMARD initiation after initial PsA diagnosis. Conclusions Time to treatment initiation was significantly longer in Black patients compared with White patients with newly diagnosed PsA. These findings suggest care delivery disparities in patients with PsA and highlight the need for future studies to understand factors that drive the observed differences in drug therapy by race/ethnicity.